The Use of Instagram Social Media as a Political Communication Tool for the Bogor Regency Regional Government in 2022-2023 - Suandi, Azril Shiva Miraj; Muhammad Prakoso Aji (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
Communication cannot be separated from human life. Technological developments in the world of communication mean that humans must follow. Social media is a way to convey political messages and get feedback from communications. Political participation is a continuation of political communication used on social media. This research aims to determine the use of social media Instagram as a political communication tool by the Bogor Regency Government in 2022-2023. The research method used is qualitative with a case study method. Data collection was carried out through interviews with the Head of the Public Communications Team of the Bogor Regency Communication and Information Service directly. The results of this research found that social media, especially Instagram, was used as a means for branding regional heads and their supporting instruments. The use of Instagram social media is used as a means to convey political messages such as the regional head's vision and mission, the regional head's agenda as well as promoting MSMEs and regional tourism potential. Evaluations are carried out by the Communication and Information Service periodically based on issues circulating in the community.